Public health policy decisions on medical innovations: what role can early economic evaluation play? - Susanne Hartz; Jürgen John (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Our contribution aims to explore the different ways in which early economic data can inform public health policy decisions on new medical technologies. Methods: A broad explorative literature research was conducted to detect methodological contributions covering the health policy perspective. Results: Early economic data on new technologies can support public health policy decisions in several ways. Embedded in horizon scanning and HTA activities, it adds to monitoring and assessment of innovations. It can play a role in the control of technology diffusion by informing coverage and reimbursement decisions as well as the direct public promotion of health care technologies, leading to increased efficiency. Major problems include the uncertainty related to economic data at early stages as well as the timing of the evaluation of an innovation. Conclusions: Decision-makers can benefit from the information supplied by early economic data, but the actual use in practice is difficult to determine. Further empirical evidence should be gathered, while the use could be promoted by further standardization.
Keywords: 330; economic evaluation; early data; innovation; public health policy decision-making; Medizintechnisches Gerät; Technikbewertung; Wirtschaftlichkeit; Frühwarnsystem; Gesundheitspolitik; Politische Entscheidung; Publikationsanalyse; Welt